Accounting in the Fourth Industrial Revolution: from the perspective of accounting professionals from Abaeté and from the students of the accounting sciences course at UEMG, Abaeté unit (Research, Society and Development, 2022)
The article will address the effects of the Fourth Industrial Revolution and the future of the accounting profession, referring to technological evolution. It is intended to answer what are the perspectives of accounting professionals and students of the Accounting Sciences Course at UEMG/Abaeté on the future of the accounting profession, after the advances provided by the Fourth Industrial Revolution. The methodology used will be qualitative research, through data collection and presentation in graphs and tables. The nature of the research is applied and exploratory, as it is a new subject, but one that inhabits professional and academic environments. It will be descriptive, therefore, a questionnaire will be applied to office owners and students from UEMG - Abaeté, it will be a field research being the target audience, Accountants from the municipality of Abaeté, Minas Gerais and students from the University of the State of Minas Gerais - UEMG Abaeté Unit. Intentional probabilistic sampling will be used, implying that everyone has knowledge about the subject, even if at a different level. According to the authors, there are risks for some professions, but having the adequate knowledge for the various aspects of Industry 4.0, it will be possible to remain in the market. The results pointed to a certain knowledge about the challenges to be faced with the new technologies arising from the Fourth Industrial Revolution.